Short Video Marketing and Collaboration Brand Network Configuration in Indonesia Skincare Market - Sukarnadi, Natalia; Lemy, Diena Mutiara; Kho, Ardi (Pandawan, 2026)
This study explores how brand network configuration, collaboration, and short video content marketing impact purchase intention within Indonesia's skincare market. The research is grounded in the Theory of Reasoned Action while examining the roles of brand attitude and subjective norms as mediating factors and gender's moderating effect. Using a quantitative survey method, data were collected from 260 Indonesian consumers who were actively engaged with local skincare brands and short video platforms. With brand attitude and with subjective norms considered as critical mediators, results coming from Partial Least Squares Structural Equation Modelling (PLS-SEM) reveal that collaboration brand networks, along with short video content marketing, do significantly increase purchase intention. Furthermore, the effect is more substantial within female consumers. Thus, a prominent gender moderation is indicated here. Local skincare brands should collaborate tactically, leverage short-form video content, improve consumer engagement, and make strategic purchases to highlight the findings' importance. This study applies the Theory of Reasoned Action more broadly, not only to digital and collaborative marketing contexts, but also provides brands with actionable managerial insights as they seek competitive advantage in emerging markets.